2015
DOI: 10.5194/sed-7-1263-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Jurassic–cretaceous deformational phases in the Paraná intracratonic basin, southern Brazil

Abstract: Abstract. This paper examines the domes and basins, regional arcs and synclines, and brittle structures of the Paraná Basin flood volcanism to characterize the deformational phases in its Jurassic to Cretaceous history. First-stage fieldwork revealed brittle structures, extensional joints, and strike-slip faults, and second-stage fieldwork investigated the connections of the brittle structures to both open folds and dome-and-basin features. Fault-slip data inversion was performed using two different techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
0
4
0
4
Order By: Relevance
“…Jacques, et al, ( 2014) recognized the importance of the E-W direction of σ1 paleostress caused by the compressive tectonic interaction between the Nazca and South American plates, to the generation of transpressive structures in the southern part of the Paraná Basin being nearly parallel to σ1 and perpendicular to σ3 in a compressional transpressive tectonic regime, in Santa Catarina state. Strieder, et al, (2015) also concluded that the direction of tectonic efforts represented by tectonic plates movements that were well coincident by open fault directions quite close to the E-W direction, close to σ1 direction. This author considered that a constritional regime with horizontals σ1 and σ3 were acting mainly in the Mezosoic Era and acted on all hydrostratigraphic units of the Paraná Basin.…”
Section: Evolution Of Structural Studiesmentioning
confidence: 85%
See 2 more Smart Citations
“…Jacques, et al, ( 2014) recognized the importance of the E-W direction of σ1 paleostress caused by the compressive tectonic interaction between the Nazca and South American plates, to the generation of transpressive structures in the southern part of the Paraná Basin being nearly parallel to σ1 and perpendicular to σ3 in a compressional transpressive tectonic regime, in Santa Catarina state. Strieder, et al, (2015) also concluded that the direction of tectonic efforts represented by tectonic plates movements that were well coincident by open fault directions quite close to the E-W direction, close to σ1 direction. This author considered that a constritional regime with horizontals σ1 and σ3 were acting mainly in the Mezosoic Era and acted on all hydrostratigraphic units of the Paraná Basin.…”
Section: Evolution Of Structural Studiesmentioning
confidence: 85%
“…However, in many studies, there are preferred directions that can be identified in the field and through satellite images (Rostirolla, et al, 2001). Strieder, et al, (2015) The E-W lineaments, as well as the more recent, newly formed N-S structures, are associated with the opening of the South Atlantic Ocean (130 Ma) and with the crustal flexure of the South American Plate. However, these lineaments have a secondary influence in the Paraná Basin, and rosette diagrams from several works show that the E-W and N-S directions are less frequent (Sordi, et al, 2017).…”
Section: Evolution Of Structural Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Atkinson & Meredith, 1987b), resultando em uma curva de menor e outra de maior fator de intensidade de esforço. (Freitas et al, 2006;Strugale et al, 2007;Reginato & Strieder, 2006;Nummer et al, 2014;Jacques et al, 2015;Strieder et al, 2015;Santos et al, 2019). Salvo exceções (Freitas et al, 2006;Santos et al, 2019) (Machado et al, 2012e Jacques et al, 2015.…”
Section: Análise Estruturalunclassified
“…A direção dos diques de lamprófiros, tal como as relações de corte das falhas, indicaria uma idade neocretácea a paleógena desse evento. Freitas et al, 2006;Strugale et al, 2007;Reginato & Strieder, 2006;Nummer et al, 2014;Jacques et al, 2015;Strieder et al, 2015;Santos et al, 2019 ) e foi relacionado ao campo de esforços de compressão E-W, atuante na borda leste do continente Sul-Americano, a partir do Holoceno (v.g. Assumpcao, 1992;Assumpção, 1998;Salvador & Riccomini, 1995).…”
Section: Análise Estruturalunclassified